Spectrophotometric Determination of Silymarin - Reddy, M.N.; Reddy, Y.P.N.; Reddy, P.J.; Murthy, T.K. (Asian Journal of Chemistry, 2010)
Two simple spectrophotometric methods (A and B) have been developed for the determination of silymarin in pure form and in its pharmaceutical formulations. Method A is based on the formation of blood red coloured complex with ferric chloride and 1,10- phenanthroline having absorption maximum at 510 nm. In method B, silymarin forms blue coloured complex with Folin-cioCalteu (FC) reagent in the presence of sodium hydroxide exhibiting maximum absorption at 740 nm. The chromogens obey Beer's law in tlfe concentration ranges of 2.5 to 25 μg/mL and 2.5 to 20 μg/mL for methods A and B respectively.